Mortality and Readmissions After Cervical Fractures From Falls In Older Adults: A Comparison To Hip Fractures Using National Medicare Data - Cooper, Zara (J Am Geriatr Soc, 2015)
BACKGROUND: Cervical fractures from falls are a potentially lethal injury in older patients. Little is known about their epidemiology and outcomes. OBJECTIVES: To examine the prevalence of cervical spine fractures after falls among older Americans and show changes in recent years. Further, to compare 12-month outcomes in patients with cervical and hip fracture after falls. DESIGN, SETTING, AND PARTICIPANTS: A retrospective study of Medicare data from 2007–2011 including patients ≥65 with cervical fracture and hip fracture after falls treated at acute care hospitals. MEASUREMENTS: Rates of cervical fracture, 12-month mortality and readmission rates after injury. RESULTS: Rates of cervical fracture increased from 4.6/10,000 in 2007 to 5.3/10,000 in 2011, whereas rates of hip fracture decreased from 77.3/10,000 in 2007 to 63.5/10,000 in 2011. Patients with cervical fracture without and with spinal cord injury (SCI) were more likely than patients with hip fracture, respectively, to receive treatment at large hospitals (54.1%, 59.4% vs. 28.1%, p< 0.001), teaching hospitals (40.0%, 49.3% vs. 13.4%, p< 0.001), and regional trauma centers (38.5%, 46.3% vs. 13.0%, p< 0.001). Patients with cervical fracture, particularly those with SCI, had higher risk-adjusted mortality rates at one year than those with hip fracture (24.5%, 41.7% vs. 22.7%, p<0.001). By one year, more than half of patients with cervical and hip fracture died or were readmitted to the hospital (59.5%, 73.4% vs. 59.3%, p<0.001). CONCLUSION: Cervical spine fractures occur in one of every 2,000 Medicare beneficiaries annually and appear to be increasing over time. Patients with cervical fractures had higher mortality than those with hip fractures. Given the increasing prevalence and the poor outcomes of this population, hospitals need to develop processes to improve care for these vulnerable patients.